Deconstructing the myths of Islamic art
1 online resource
Keywords: "Deconstructing the Myths of Islamic Art addresses how researchers can challenge stereotypical notions of Islam and Islamic art while avoiding the creation of new myths and the encouragement of nationalistic and ethnic attitudes. Despite its Orientalist origins, the field of Islamic art has continued to evolve and shape our understanding of the various civilizations of Europe, Africa, Asia, and the Middle East. Situated in this field, this book addresses how universities, museums, and other educational institutions can continue to challenge stereotypical or homogeneous notions of Islam and Islamic art. It reviews subtle and overt mythologies through scholarly research, museum collections and exhibitions, classroom perspectives, and artists' initiatives. This collaborative volume addresses a conspicuous and persistent gap in the literature, which can only be filled by recognizing and resolving persistent myths regarding Islamic art from diverse academic and professional perspectives. The book will be of interest to scholars working in art history, museum studies, visual culture, and Middle Eastern studies"--